Rencana Keberhasilan Reklamasi Pada Kegiatan Penambangan Bijih Nikel PT. Bhumi Karya Utama, Kabupaten Konawe Utara, Sulawesi Tenggara - Anisa Sapana, Erin; Supandi; Shilvyanora Aprilia Rande (Retii, 2023)
Mining activities have had both positive and negative impacts on the environment. The biggest negative impact is land and soil degradation which causes expansion of critical land, loss of surface layer, loss of soil organic matter, and damage to environmental ecosystems. One way to improve or restore the environmental conditions of former mining activities is to revegetate. The purpose of this research is to find out and make plans for land management that will be carried out of reclamation activities, make and know plans for revegetation activities carried out as part of reclamation activities, as wellas calculating and knowing the estimated costs for reclamation activities. The research method used is qualitative wich is focused on observing the area to be reclaimed. The total area of the mining area is 310 Ha, with a total planned area to be reclaimed in 2022 of 14.70 Ha which will be carried out in stages and starting in the Blok. Utara, Pit. Nakula 1 Selatan with an area of 1.65 Ha and requires a plant of 1,031 trees. From this research it can be seen that the planned total needs for overburden and topsoil will later be used as backfilling in the Block area. North, Nakula Pit 1 South is 16,500 . The types of plants that will be used in revegetation activities are covercrop (Centrosema Pubescens and Pueraria Javanica), pioneer plants (Circumber and Teak) and insert trees (Cashew). The estimated cost of this reclamation activity plan is Rp.332.244.500. Reclamation planning in this study can be said to be successful because it has fulfilled and followed the steps contained in Kepmen ESDM No. 1827 K/30/MEM/2018.